PENGARUH PEMANFAATAN BEASISWA PROGRAM INDONESIA PINTAR (PIP) TERHADAP MOTIVASI BELAJAR SISWA - Kaunang, Irmalia; Abdul, Irawati; Maruwae, Abdulrahim; Bumulo, Frahmawati; Bahsoan, Agil (Damhil Education Journal, 2024)
The PIP Scholarship is a government program that aims to help students from underprivileged families still be able to access good education. PIP scholarships can cause students to lack understanding of the value of education because their main focus is getting scholarship funds. As a result, they may not appreciate the importance of the learning process and prioritize academic achievement alone. This research aims to determine the influence of the Smart Indonesia Scholarship Program on the learning motivation of Class VIII students at SMP Negeri 3 Gorontalo. In its implementation, this research used a correlational quantitative approach with a sample size of 40 students. Data was collected based on observation, interviews, questionnaires, documentation and analyzed using simple regression analysis. The research findings show that there is a positive and significant influence of the Smart Indonesia Scholarship Program on the Learning Motivation of Class VIII students at SMP Negeri 3 Gorontalo. Based on regression analysis, a coefficient of determination value of 0.332 was obtained, indicating that 33.2% of the variation in the Smart Indonesia Scholarship Program was handled by student learning motivation. In other words, the better the use of the Smart Indonesia Scholarship Program, the greater the student's motivation to learn. Meanwhile, the remaining 66.8% was influenced by other variables not examined in this research.